Glucose uptake : stimulatory activity of Gynura procumbens in 3T3- F442A adipocytes - Mohd. Bohari, Siti Pauliena; Hamid, Muhajir; Shaari, Khozirah; Lajis, Nordin (UNIMAS and Malaysian Natural Products Society, 2006)
Gynura procumbens (Compositae) has been used as folk remedy for the treatment to control diabetes mellitus and hyperlipidemia. The aim of this study was to examine whether G. procumbens extract for various solvent system had an enhancing effect on glucose uptake in 3T3 adipocyte cell lines. At the concentration 0.1mg/mL of hexane fraction showed increase in glucose uptake activity 4.5 fold whereas etyl acetate fraction increased 2.2 fold at 0.005 mg/mL of compare to untreated. For butanol fraction showed dependent manner of insulin and at 0.05mg/mL of extract, glucose uptake activity was increased 1.4 fold compare to the insulin.These results suggest that the antidiabetic action of G. procumbens may be mediated throught the stimulation of glucose uptake and the potentiation of insulin action.